IMPLEMENTATION OF DEMOCRATIC SCHOOL PRINCIPAL LEADERSHIP STYLE IN INFLUENCING TEACHER PERFORMANCE TO IMPROVE TEACHER COMPETENCE - Fikri Rosyid, Ahmad; Rindaningsih, Ida (Antis-Publisher, 2024)
Objective: This study aims to identify and analyze the implementation of a democratic principal's leadership style in enhancing teacher competence and performance at SD Muhammadiyah 2 Krian. Method: A descriptive method with a qualitative approach was applied. Data collection techniques included observation, documentation, and interviews to gather comprehensive insights into the leadership practices and their impact. Results: Findings revealed that the democratic leadership style of the principal significantly influenced teacher performance and competence improvement. The principal actively listened to complaints and suggestions from teachers, fostering open communication. Teachers were encouraged to participate in decision-making processes. Strategies implemented to enhance teacher competence included providing motivation, recognizing achievements through awards, conducting teacher training programs, and supporting teachers in pursuing higher education. Novelty: This study highlights the pivotal role of a democratic leadership style in educational settings, specifically in enhancing teacher competence. The emphasis on participatory decision-making and tailored strategies for professional development offers a practical model for leadership in schools aiming for teacher empowerment and performance improvement.